Makna Hidup Harmoni dengan Komodo dalam Perspektif Masyarakat Adat Ata Modo: Sebuah Studi Fenomenologis - Hidayat, Arif; Arfah, Muh; Susanti, Nety; Nurlatifah, Halimah; Sipirunaung, Dikiwahyudi; Monica, Della; Jeffry Parsi, Muhammad (Universitas Andalas, 2025)
This research aims to explore the meaning of harmonious living with Komodo dragons from the perspective of the Ata Modo indigenous community in Rinca Island, East Nusa Tenggara. Komodo dragons are not only protected endangered animals, but also creatures that are culturally integrated into the spiritual and cosmological values of the local community. Using a hermeneutic phenomenological approach, this study explores the lived experiences, oral narratives, and values contained in the interaction between humans and Komodo dragons. The results show that the harmony of living with Komodo dragons is understood as a form of spiritual sustainability, ecological balance, and an expression of respect for ancestors and nature. These findings enrich the intercultural perspective in cultural ecology studies and provide a reflective basis for community-based conservation policy development. Data were collected through in-depth interviews with traditional leaders, senior citizens and local conservationists. References were obtained from relevant national and international literature. This study emphasizes the importance of understanding conservation not only ecologically but also through cultural and phenomenological dimensions.